TO STUDY TYPES OF PRESENILE CATARACT AND ITS RISK FACTORS AT A TERTIARY HEALTH CARE CENTRE IN EAST BIHAR - RAJEETA BASUR; REENA KUMARI; DINESH KUMAR BHAGAT (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: A cataract is defined as opacity within the clear lens inside the eye that reduces the amount of incoming light and results in deterioration of vision. Cataract is considered as one of the most common causes of visual defect or impairment in the world. According to the World Health Organization, cataract is the leading cause of blindness all over the world, responsible for 47.8% of blindness and accounting for 17.7 million blind people. In India, the major cause of blindness is cataracts, which accounts for 62.6%. However, detailed epidemiological data on types of presenile cataracts and its risk factors, especially in regions, such as Eastern Bihar, are sparse. (1) To determine the proportion of different types of presenile cataracts and (2) Risk factors associated with the occurrence of presenile cataracts. Methods: Patients in the age group of 20–50 years attending the tertiary Health care center out-patient clinic of the Ophthalmology Department who were found to have presenile cataracts were to be recruited as cases. Those who gave consent to participate in the study were interviewed and underwent a complete ocular examination. Results: The thesis presents a detailed analysis of cataract types and their distribution among 165 cases based on various demographic, occupational, and clinical factors. The most prevalent cataract type was nuclear sclerosis plus posterior subcapsular cataract (30.3%), followed by mature cataract and posterior subcapsular cataract (both 15.2%). Alcohol consumption (12.7%) and smoking (11.5%) were the most prevalent risk factors. Conclusion: This comprehensive study on cataract epidemiology revealed nuclear sclerosis plus posterior subcapsular cataract as the most prevalent type, with a higher incidence among older adults, females, individuals from lower socioeconomic backgrounds, and those with occupations involving prolonged sun exposure, such as farming and housework.